Expression of a Bacterial Trehalose-6-phosphate Synthase otsA Increases Oil Accumulation in Plant Seeds and Vegetative Tissues - Zhai, Zhiyang; Keereetaweep, Jantana; Liu, Hui; Feil, Regina; Lunn, John E.; Shanklin, John (Frontiers in Plant Science, 2021)
We previously demonstrated that exogenous trehalose 6-phosphate (T6P) treatment stabilized WRINKLED1 (WRI1), a master transcriptional regulator of fatty acid synthesis and increased total fatty acid content in Brassica napus (B. napus) embryo suspension cell culture. Here we explore Arabidopsis lines heterologously expressing the Escherichia coli T6P synthase (otsA) or T6P phosphatase (otsB) to refine our understanding regarding the role of T6P in regulating fatty acid synthesis both in seeds and vegetative tissues. Arabidopsis 35S:otsA transgenic seeds showed an increase of 13% in fatty acid content compared to those of wild type while seeds of 35:otsB transgenic seeds showed a reduction of 12% in fatty acid content compared to wild type. Expression of otsB significantly reduced the level of WRI1 and expression of its target genes in developing seeds. Like Arabidopsis seeds constitutively expressing otsA, transient expression of otsA in Nicotiana benthamiana leaves resulted in strongly elevated levels of T6P. This was accompanied by an increase of 29% in de novo fatty acid synthesis rate, a 2.3-fold increase in triacylglycerol (TAG) and a 20% increase in total fatty acid content relative to empty vector controls. Taken together, these data support the heterologous expression of otsA as an approach to increasing TAG accumulation in plant seeds and vegetative tissues.